2018
DOI: 10.1017/s0007114518001526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SCFA on the DNA methylation pattern of adiponectin and resistin in high-fat-diet-induced obese male mice

Abstract: Specific adipokines, such as adiponectin and resistin, are secreted from adipose tissue and are associated with the development of obesity. Supplementation of dietary SCFA can prevent and reverse high-fat-diet (HFD)-induced obesity. However, it is not clear whether SCFA ameliorate abnormal expression of adiponectin and resistin in the obese state. The aim of this study was to investigate the effects of SCFA on adiponectin and resistin's expressions in diet-induced obese mice, as well as the potential mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…In contrast, a higher SCFA content in feces of obese humans was found and a higher concentration of butyrate and acetate was measured in the caeca of obese mice [52,53]. Nonetheless, previously, we have demonstrated that the lower mRNA levels of adiponectin and resistin in obese mice can be reversed to normal range by dietary supplementation of SCFAs, and these effects may be involved in epigenetic modifications through directly reducing the expression of DNMT1, DNMT 3a, and DNMT3b and suppressing the binding of these enzymes to the promoters of adiponectin and resistin [54]. In the present study, with antibiotic use, fecal SCFA contents were reduced due to the reduction of SCFA-producing bacteria including the phylum Firmicutes and the genera of Faecalibaculum, Ruminococcaceae, Lactobacillus, and Bifidobacterium [55,56], which was not concomitant with the reduced methylation fractions of CpG sites at the promoters of adiponectin and resistin and the downregulated DNMT1 expression in the high-fat diet feeding.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, a higher SCFA content in feces of obese humans was found and a higher concentration of butyrate and acetate was measured in the caeca of obese mice [52,53]. Nonetheless, previously, we have demonstrated that the lower mRNA levels of adiponectin and resistin in obese mice can be reversed to normal range by dietary supplementation of SCFAs, and these effects may be involved in epigenetic modifications through directly reducing the expression of DNMT1, DNMT 3a, and DNMT3b and suppressing the binding of these enzymes to the promoters of adiponectin and resistin [54]. In the present study, with antibiotic use, fecal SCFA contents were reduced due to the reduction of SCFA-producing bacteria including the phylum Firmicutes and the genera of Faecalibaculum, Ruminococcaceae, Lactobacillus, and Bifidobacterium [55,56], which was not concomitant with the reduced methylation fractions of CpG sites at the promoters of adiponectin and resistin and the downregulated DNMT1 expression in the high-fat diet feeding.…”
Section: Discussionmentioning
confidence: 86%
“…Butyrate is produced by the microbial fermentation of undigested polysaccharides that reach the colon [42]. In addition, butyrate also plays a crucial role in influencing gene expression in host colonic cells via epigenetic regulation [43,44]. In human cells, there is evidence that butyrate has a direct effect on DNA methylation by regulating key enzymes, including methylcytosine dioxygenase (TET) and DNA methyltransferase 1 (DNMT1) [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we found a positive correlation between hypomethylations of GLP1-R and succinate in the ileum but a negative correlation between hypomethylation of GLP1-R and acetic acid in the colon. The possible effect of acetic acid on DNA methylation was suggested by the administration of acetate and/or other SCFA to prevent body weight gain in male mice with high-fat diet-induced obesity [54]. Moreover, the different profiles of the correlations between the ileum and the colon may be related to the different methylation patterns in these tissues, which may also indicate possible changes in microbiota.…”
Section: Discussionmentioning
confidence: 99%